The exchange rate regime of the WAEMU: Monetary stability at the expense of current account deficits and rising external financial liabilities? A post-Keynesian view - Florian Lampe (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2024)
The West African Economic and Monetary Union (WAEMU) is a currency and customs union that is made up of the eight low-income countries Benin, Burkina Faso, Côte d'Ivoire, Guinea-Bissau, Mali, Niger, Senegal, and Togo. Except for Guinea-Bissau, all member countries of the WAEMU have a shared history as former French colonies. The WAEMU's common currency, the CFA franc, is today pegged to the euro at a fixed exchange rate that is guaranteed by the French treasury. France's influence on monetary policy issues of the WAEMU is still highly present and increasingly contested by political economists, and part of the member countries' civil society. These critics denounce the bilateral exchange rate arrangements as monetary colonialism that outlasted the political independence process from 1954 till 1960 and prevents the West African countries from implementing growth-oriented macroeconomic policies. The proponents of the fixed exchange-rate regime emphasize monetary stability in the form of relatively low inflation rates and a stable external value of the domestic currency. Indeed, the WAEMU zone has shown a remarkably long period of exchange rate stability for the past 30 years. This distinguishes it from Developing and Emerging Economies (DEE) in Latin American or Asian countries in the 1990s and early 2000s, which reacted to balance of payments crises with the introduction of floating exchange rate regimes. The present paper connects to that controversial debate and addresses the important research question if the argument of monetary stability holds considering the current development path of the WAEMU. More concretely, it contrasts the monetary union's resilience against the adverse effects of exchange rate volatility with international competitiveness and a long-term perspective on external debt. On the theoretical level, the study draws on the post-Keynesian liquidity preference theory to elaborate the exchange rate challenges that DEE with internationally integrated financial markets are confronted with. This approach highlights the hierarchical structure of the international monetary system and the resulting adverse implications for peripheral currency areas regarding monetary stability. Furthermore, monetary Keynesian economist have worked out the limitations of an exchange rate-based stabilization strategy arguing that it comes at the expense of losing international competitiveness and a rising international debtor position. These findings serve as a theoretical basis for studying the sustainability of the WAEMU's development path.
Keywords: 330; WAEMU; CFA franc; Post-Keynesian Economics; international currency hierarchy